Input-Output Analysis in the Policy-Making Process: An Analysis of the Systems Theory - Pulami Magar, Rudra Bahadur (Chaturbhujeshwar Academic Journal, 2025)
This study examines the policy-making process through the theoretical lenses of systems theory and input-output analysis. Systems theory conceptualizes the state as an open, dynamic system that responds to environmental demands by producing policies, decisions, laws, or programs, and continuously revises them based on feedback. Employing qualitative analysis of secondary sources including books, academic articles, and policy documents from international organizations this research highlights that policy-making in transitional democracies and developing societies like Nepal extends beyond formal institutions to include social movements, citizen activism, interest groups, and international factors. The systems theory framework elucidates these complex interrelationships, while the input-output model identifies challenges related to policy efficiency, accountability, and legitimacy. The findings underscore the importance of a feedback-based approach to reform Nepal’s policy system, aiming to enhance policy stability, accountability, and public trust.